2016
DOI: 10.3390/ma9121010
|View full text |Cite
|
Sign up to set email alerts
|

Two-Level Micro-to-Nanoscale Hierarchical TiO2 Nanolayers on Titanium Surface

Abstract: Joint replacement is being actively developed within modern orthopedics. One novel material providing fast implantation is bioactive coatings. The synthesis of targeted nanocoatings on metallic nanotitanium surface is reported in this paper. TiO2-based micro- and nanocoatings were produced by sol-gel synthesis using dip-coating technology with subsequent fast (shock) drying in hot plate mode at 400 °C. As a result of shock drying, the two-level hierarchical TiO2 nanolayer on the nanotitanium was obtained. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Using this approach, we fabricated a nanoporous layer with micron-sized defects. This article continues our previous work [21], in which we showed the effect of acceleration of osteoblast-like cell adhesion after this kind of modification. More detailed evaluation of the efficiency was based on a deep cytological analysis that included the study of the marker levels of the osteoblast-like cell differentiation, meaning the mineralization of the peri-implant area.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Using this approach, we fabricated a nanoporous layer with micron-sized defects. This article continues our previous work [21], in which we showed the effect of acceleration of osteoblast-like cell adhesion after this kind of modification. More detailed evaluation of the efficiency was based on a deep cytological analysis that included the study of the marker levels of the osteoblast-like cell differentiation, meaning the mineralization of the peri-implant area.…”
Section: Introductionsupporting
confidence: 88%
“…Thus, xerogel films were obtained. As we showed in our earlier work [21], this method leads to anatase.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…In the current study, we applied the method of ML-ALD that provided the possibility to efficiently and precisely obtain the required surface microtopographic/nanotopographic parameters ( Figure 4; Table 3). The efficacy of this approach could be compared to the currently employed methods including anodic oxidation, plasma deposition, chemical vapor deposition, sol-gel synthesis, 43 thermal spray deposition, and electrostatic spray. 31,34 In the series of in vitro experiments, we clearly demonstrated that hierarchical microtopographic/ nanotopographic coatings significantly enhanced osteogenic cell differentiation of mouse MC3T3-E1 osteoblasts ( Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…These composites with excellent performance are promising for application in electrode/collector materials [ 16 , 17 ]. The transition metal oxides [ 18 , 19 , 20 ] are considered to be promising candidates for anode materials owing to their high electrochemical capacities. Many studies on iron oxides have also been performed with the aim of improving the battery performance of cathode materials [ 21 , 22 ] and removing anionic and aromatic dyes from wastewater [ 23 ].…”
Section: Resultsmentioning
confidence: 99%